Proceedings of the 5th European Conference on Computer Systems 2010
DOI: 10.1145/1755913.1755950
|View full text |Cite
|
Sign up to set email alerts
|

The next 700 BFT protocols

Abstract: Modern Byzantine fault-tolerant state machine replication (BFT) protocols involve about 20,000 lines of challenging C++ code encompassing synchronization, networking and cryptography. They are notoriously difficult to develop, test and prove. We present a new abstraction to simplify these tasks. We treat a BFT protocol as a composition of instances of our abstraction. Each instance is developed and analyzed independently.To illustrate our approach, we first show how our abstraction can be used to obtain the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 21 publications
(32 reference statements)
2
156
0
2
Order By: Relevance
“…Previous works (e.g., Zyzzyva [14] or PBFT [5]) have shown that the bottleneck in BFT protocols is actually cryptography, not network usage. Interestingly, the BFT protocol that currently provides the highest throughput uses TCP [11]. This protocol, called Chain, implies the smallest number of cryptographic operations at the bottleneck replicas, hence its very good performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works (e.g., Zyzzyva [14] or PBFT [5]) have shown that the bottleneck in BFT protocols is actually cryptography, not network usage. Interestingly, the BFT protocol that currently provides the highest throughput uses TCP [11]. This protocol, called Chain, implies the smallest number of cryptographic operations at the bottleneck replicas, hence its very good performance.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative could be to change the master instance to the instance which provides the highest throughput. This would require a mechanism to synchronize the state of the different instances when switching, similar to the switching mechanism of Abstract [11]. We will explore this design in our future work.…”
Section: A Protocol Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…PERFORMANCE EVALUATION In this section we evaluate the performance of ByzID by comparing it with three well-known BFT protocols-PBFT [6], Zyzzyva [27], Aliph [21], and an implementation of the crash fault tolerant protocol-Paxos [29]. All of the protocol implementations are based on Castro et al's implementation of PBFT.…”
Section: Theorem 2 (Liveness)mentioning
confidence: 99%
“…Such RSMs are referred to as Byzantine faulttolerant (BFT). Despite significant progress in making BFT practical [6,21], it has not been widely adopted, mainly because of the complexity of the techniques involved and high overheads. In addition, BFT is not a panacea, since there are a variety of attacks, such as various performance attacks that BFT does not handle well [2,9].…”
Section: Introductionmentioning
confidence: 99%